2004
DOI: 10.1051/0004-6361:20041077
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear electromagnetic modes in astrophysical plasmas with dust distributions

Abstract: Abstract.A derivative nonlinear Schrödinger equation is obtained for parallel electromagnetic modes in plasmas containing polydisperse charged dust. The coefficient of the dispersive term in that equation is dominated by the dust rather than the (plasma) ions, and polydisperse dust yields a larger coefficient in absolute value than an equivalent monodisperse description. This leads to a significant broadening of the nonlinear structure due to the presence of polydisperse rather than monodisperse dust, the latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Verheest (2004) applied the reductive perturbation theory to derive a DNLS to describe the nonlinear evolution of parallel propagating electromagnetic waves in multispecies plasmas; he showed that the DNLS cannot have stationary solitary waves, only envelope solitons. Verheest and Cattaert (2004) derived a DNLS for parallel electromagnetic modes in plasmas containing polydisperse charged dust; they showed that when modeling the charged dust by a power-law distribution in planetary rings and other astrophysical systems, it depends very much on the power-law index whether the smaller or the larger grains are more important. Pandey et al (2008) studied the nonlinear wave propagation in collisional dusty plasma when electrons and ions are highly magnetized so that the Lorentz force acting on the plasma particles dominates its collision with the dust and charged dust remains weakly magnetized; they showed that large-amplitude waves can be easily excited in such a collisional dusty medium and can be described by the DNLS, whose soliton solutions explain the parsec scale structures in astrophysical plasmas.…”
Section: Alfvén Chaosmentioning
confidence: 99%
“…Verheest (2004) applied the reductive perturbation theory to derive a DNLS to describe the nonlinear evolution of parallel propagating electromagnetic waves in multispecies plasmas; he showed that the DNLS cannot have stationary solitary waves, only envelope solitons. Verheest and Cattaert (2004) derived a DNLS for parallel electromagnetic modes in plasmas containing polydisperse charged dust; they showed that when modeling the charged dust by a power-law distribution in planetary rings and other astrophysical systems, it depends very much on the power-law index whether the smaller or the larger grains are more important. Pandey et al (2008) studied the nonlinear wave propagation in collisional dusty plasma when electrons and ions are highly magnetized so that the Lorentz force acting on the plasma particles dominates its collision with the dust and charged dust remains weakly magnetized; they showed that large-amplitude waves can be easily excited in such a collisional dusty medium and can be described by the DNLS, whose soliton solutions explain the parsec scale structures in astrophysical plasmas.…”
Section: Alfvén Chaosmentioning
confidence: 99%
“…We think this is the right word to describe unexpected pairings of methods with astronomical entities, for instance (a) "application of group theory to the problem of solar wind expansions" (Kalisch et al 2003), (b) "fractional Brownian motion" as a description of turbulence in the interstellar medium (Levrier 2004), (c) the use of Schroedinger's equation to describe electromagnetic modes in a dusty plasma (Verheest & Cattaert 2004), (d) a path integral formalism to describe a gravitational instability (Valageas 2004). R. P. Feynman is duly cited, and remember it was not he who made fun of the existence of an institute of "quantum oceanology" but S. W. Hawking, (e) a Wein fire-ball as initial conditions for jet collimation in active galactic nuclei (Iwamoto & Takahara 2004), (f) generalized entropy as a way of understanding why the lowest-energy state for the interplanetary medium has a bimodal distribution of particle energies (Leubner 2004), and (g) solitons, not for spiral density waves or even as a way of preserving the ordained ratios of horses to horse parts, but as a description of the sand dunes called barchans (Schwammle & Herrmann 2003).…”
Section: Interdisciplinaritymentioning
confidence: 99%